Unveiling patterns: a data-driven exploration of overseas residents' views on Qingdao's tourism development - Sahand Abdinematabad; Roghaye Ebadikhah; Mehdi Pourabdollah; Reza Rasinojehdehi (Computational Algorithms and Numerical Dimensions)
This study embarks on a data-driven exploration to understand the perceptions of overseas residents regarding the development of tourism in Qingdao, a significant coastal city in China. Despite the pivotal role of tourism in regional economic growth, the views of foreign residents, who can act as cultural ambassadors, have been relatively underexplored in existing literature. This research fills this gap by conducting a comprehensive questionnaire survey among Qingdao's overseas community. The survey aims to gather insights into the economic, socio-cultural, and environmental impacts of tourism as perceived by this unique demographic. The study utilizes advanced computational methods to analyze the collected data, offering a nuanced understanding of how variables such as age, income, and personal connections to tourism influence these perceptions. The findings reveal diverse viewpoints, shaped by various demographic factors, highlighting the complexity of tourism impact assessment from the perspective of foreign residents. This research contributes to the broader discourse on sustainable tourism development, providing valuable inputs for policymakers and stakeholders in Qingdao to tailor tourism strategies that are more inclusive and representative of all residents' views. The results have broader implications for understanding the role of foreign residents in shaping the tourism landscape in global destinations.